E‐cigarettes and respiratory health: the latest evidence. (18th June 2020) - Miyashita, Lisa; Foley, Gary
Abstract: The E‐cigarette market continues to expand at an alarming rate with thousands of flavours available for purchase and continuously evolving devices. Now that it is a multi‐billion dollar industry and one without stringent regulation, there is rising concern over the safety of vaping products. Since June 2019, over 2800 cases of E‐cigarette‐associated acute lung toxicity have been reported in the USA, over 60 of which resulted in death. Many argue that E‐cigarettes offer a safer alternative to smoking, but we are evidently far from fully understanding the potential hazards that they pose to respiratory health. Although the risk of an outbreak in the UK has been considered low due to tighter E‐cigarette regulations, we cannot fully eliminate the possibility of similar events occurring in the future. With evidence frequently emerging of the harmful effects of E‐cigarettes to pulmonary health, there is an urgent need to define the long‐term implications of vaping. Studies show that E‐cigarette exposure can disrupt pulmonary homeostasis, with reports of gas exchange disturbance, reduced lung function, increased airway inflammation and oxidative stress, downregulation of immunity, and increased risk of respiratory infection. In this review, the latest research on the effect of E‐cigarette use on respiratory health will be presented. Abstract : Abstract figure legend : Overview of E‐cigarette induced lung injury and immune response within the human respiratory system